PENERAPAN LAPORAN KEUANGAN BAGI USAHA MIKRO DAN KECIL DI WILAYAH CIRACAS JAKARTA TIMUR - Dwi Jaya Kirana; Yoyoh Guritno (Universitas 17 Agustus 1945 Jakarta, 2019)
This study aims to determine how the application of financial statements for Micro and Small Business Owners (MSEs) is applied in understanding and quality of financial statements in the Ciracas Region of East Jakarta. This research is a qualitative method that uses the interpretive paradigm and ethnomethodology approach. Techniques for collecting data with observation, surveys, interviews, and documentation. Informants were randomly selected using the Micro and Small Sector Business criteria in Ciracas Subdistrict and participating in One Center Entrepreneurship (OK OCE) sub-district activities during 2018. The results showed that Micro Small Enterprises under the auspices of OK OCE Ciracas in East Jakarta was still lacking in understanding and quality of reporting. finance and some informants indicated that they did not need financial statements.